Biomechanical comparison of two InternalBrace™ reinforced thumb ulnar collateral ligament reconstruction techniques. (December 2022) - Rigó, István Zoltán; Riano, Felix; Kalapos, Robert; Haugstvedt, Jan-Ragnar
Abstract: Background: Chronic ulnar collateral ligament ruptures of the thumb metacarpophalangeal joint are often not eligible for direct surgical repair and ligament reconstruction could be considered. Several reconstruction techniques are published, with different types of configurations and fixation methods of the tendon grafts. However, failure of the reconstruction with recurrent instability is still a problem, despite stable graft to bone fixation. Augmentation of the free tendon graft with non-resorbable suture material is gaining popularity, aiming to withstand elongation or rupture of the graft. The purpose of this study was to compare two different augmented ulnar collateral ligament reconstruction methods in a cadaver model. Methods: Ten matched pairs of cadaveric upper extremities were used. The thumbs were disarticulated at the trapezometacarpal joint and the ulnar collateral ligament was excised then reconstructed with Internal Brace™ reinforced tendon graft, which was fixed to the bones using either a Tenodesis screw or DX Swivelock® anchor. The thumbs were biomechanically tested with valgus stress, while the force and displacement were simultaneously measured and plotted. Findings: The mean (SD) load at clinical failure and maximum load were 19.4 (5.3) and 31.4 (9.5) N in the Tenodesis group, and 21.0 (10.0) and 31.4 (13.9) N in the DX SwiveLock® group, respectively. None of these differences were significant. These results are comparable with previous publications. Interpretation: The Tenodesis screw and the DX SwiveLock® thumb ulnar collateral ligament reconstruction with Internal Brace™ reinforced free tendon graft showed equal strength, both methods are feasible alternatives in the clinical setting. Highlights: Thumb ulnar collateral ligament reconstruction with tendon graft is a common procedure. Internal brace reinforcement can increase the strength of the reconstruction. Modern anchor materials allow stable fixation of the graft. Swivelock anchors provide similar strength to interference screws.